Total synthesis and mechanism of action of the antibiotic armeniaspirol A. Issue 48 (1st December 2021) - Arisetti, Nanaji; Fuchs, Hazel L. S.; Coetzee, Janetta; Orozco, Manuel; Ruppelt, Dominik; Bauer, Armin; Heimann, Dominik; Kuhnert, Eric; Bhamidimarri, Satya P.; Bafna, Jayesh A.; Hinkelmann, Bettina; Eckel, Konstantin; et al.
Abstract : The antibiotic armeniaspirol A depolarized bacterial and mammalian cell membranes through a protonophore activity, that accounts for its potent antibiotic effects. A total synthesis of (±) armeniaspirol A was achieved in six steps. Abstract : Emerging antimicrobial resistance urges the discovery of antibiotics with unexplored, resistance-breaking mechanisms. Armeniaspirols represent a novel class of antibiotics with a unique spiro[4.4]non-8-ene scaffold and potent activities against Gram-positive pathogens. We report a concise total synthesis of (±) armeniaspirol A in six steps with a yield of 20.3% that includes the formation of the spirocycle through a copper-catalyzed radical cross-coupling reaction. In mechanistic biological experiments, armeniaspirol A exerted potent membrane depolarization, accounting for the pH-dependent antibiotic activity. Armeniaspirol A also disrupted the membrane potential and decreased oxygen consumption in mitochondria. In planar lipid bilayers and in unilamellar vesicles, armeniaspirol A transported protons across membranes in a protein-independent manner, demonstrating that armeniaspirol A acted as a protonophore. We provide evidence that this mechanism might account for the antibiotic activity of multiple chloropyrrole-containing natural products isolated from various origins that share a 4-acylphenol moiety coupled to chloropyrrole as a joint pharmacophore. We additionally describe an efflux-mediated mechanism of resistance against armeniaspirols.